PEMAHAMAN KONSEP MAHASISWA TENTANG RING PADA MATA KULIAH STRUKTUR ALJABAR 2 DITINJAU DARI PEMIKIRAN KREATIF PADA SISWA KELOMPOK ATAS - Maya Rini Rubowo; FX. Didik Purwosetiyono; Dewi Wulandari (Universitas Muhammadiyah Ponorogo, 2017)
This research is intended to describe the students concept of the ring in the course of algebra structure 2 in terms of creative thinking in upper students. This research is included in this type of qualitative research. The subject of the study is a mathematics student who has taken the course of Structure Algebra 2 (Ring Theory). The subjects in this study are three students who have high math skills. Instrument used in research 1) Test of Concept of Ring Concept (TPKR), 2) Interview Guidelines, 3) Creative Thinking Rubric, 4) Recording Equipment, 5) Documentation. Based on the results of the study and discussion, the findings involving the students' concept of the ring in the course of algebraic structure 2 in the upper sstudent can solve the problem in terms of explaining the associative nature, explaining the nature of the identity element, explaining the nature of each element having a good inverse. However, I can not only use one solution only, but it is less diverging and able to find other solutions. At the student level still not able to meet the original indicators in creative thinking